Geohazard impact and gas reservoir pressure dynamics in the Zagros Fold-Thrust Belt: An environmental perspective - Mahsa Asghari; Zahra Maleki; Ali Solgi; Mohammad Ali Ganjavian; Pooria Kianoush (Geosystems and Geoenvironment)
The Zagros Fold-Thrust Belt (ZFTB) presents a unique intersection of geohazards and gas reservoir dynamics, shaped by the ongoing tectonic activity resulting from the collision of the Arabian and Eurasian plates. This study aims to assess the risk of earthquake-induced landslides and their impact on gas reservoir pressure dynamics – with a particular focus on the Kabir Kuh gas field – identified as a critical area for monitoring due to its vulnerability to seismic events. A novel hybrid model is introduced that integrates geographic information system (GIS) mapping, decision support system (DSS) modeling, and machine learning algorithms. By analyzing a century's worth of seismic data alongside real-time environmental parameters, the model demonstrates a predictive accuracy of 92% using Random Forest algorithms, significantly outperforming traditional methods. The findings reveal a strong correlation between seismic activity and fluctuations in gas reservoir pressure, with an average pressure change of ±150 psi observed during significant seismic events. A landslide susceptibility map was generated, pinpointing regions that require proactive management strategies, particularly where significant landslide potential threatens gas field stability. Identifying the Seymareh landslide as a monumental geological event underscores the impact of landslide hazards on gas field integrity. This research emphasizes the integration of advanced predictive techniques into seismic risk assessments, providing actionable insights for the sustainable gas reservoir management in seismically active regions. The necessity for continuous monitoring and the implementation of advanced geotechnical measures are highlighted as essential components of effective geohazard management. This study contributes to understanding the interplay between seismic hazards and gas reservoir dynamics, offering a comprehensive framework for future research and practical applications in risk management and environmental sustainability.